PENGARUH INFLASI, SUKU BUNGA, DAN PROFITABILITAS TERHADAP RETURN SAHAM (Studi Pada Industri Keuangan Non Bank Yang Terdaftar di BEI Tahun 2019-2021) - Nalsal, Pindonta (Universitas La Tansa Mashiro, 2023)
The Covid-19 pandemic has had an impact on the economy in Indonesia, one of which is stock returns in the non-bank financial industry. The size of stock returns is also influenced by internal factors represented by the profitability ratio proxied by ROA and other external factors, namely inflation and interest rates. The aim of the research is to obtain empirical evidence of the partial and simultaneous influence of inflation, interest rates and profitability on study stock returns in the non-bank financial industry. This type of research is quantitative using secondary data in the form of annual reports from the non-bank financial industry registered on the IDX for 2019-2021. Sample selection used the purposive sampling method. The data analysis used is multiple linear regression using SPSS 25. The research results show results that can be concluded that partially ROA only has an influence on stock returns while inflation and interest rates have no effect on stock returns. However, simultaneously it shows that ROA, inflation and interest rates have an influence on stock returns in the Non-Bank Financial Industry Listed on the IDX in 2019-2021.